Multisectoral Action to Combat Regional and Social Inequities in Health 2017
DOI: 10.26911/theicph.2017.011
|View full text |Cite
|
Sign up to set email alerts
|

Biological, Physical, Social, and Environmental Factors Associated With Dengue Hemorrhagic Fever in Nganjuk, East Java

Abstract: Background: Dengue Hemorrhagic Fever (DHF) is an infectious disease transmitted by mosquitoes that carry dengue virus (DV). This disease is endemic in more than 100 countries. Nganjuk district, East Java, is a DHF endemic area with sharp increase in DHF incidence by 286% from 2014 to 2015, of which 9 cases died. This study aimed to examine biological, physical, social, and environmental factors associated with dengue hemorrhagic fever in Nganjuk, East Java. Subjects and Method: This study was observational ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This study supported the research of Sukowinarsih and Cahyati in Semarang which stated that the larvae at the water reservoir (TPA) can affect the incidence of dengue by 3.38 times greater for experiencing DHF (Sukowinarsih and Cahyati, 2010). The results of research conducted by Nurrochmawati, et al (2017) showed that there was a relationship of the presence of WR with no cover that have the potential to became a place for mosquitoes to breed that was 11.42 times more likely to suffer from HDF. The presence of WR played an important role in the density of the Aedes aegypti mosquito vector, because more and more WR sites would increase the breeding places and would be more densely populated by the Aedes aegypti mosquito (Dash et al, 2012).…”
Section: Multivariate Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…This study supported the research of Sukowinarsih and Cahyati in Semarang which stated that the larvae at the water reservoir (TPA) can affect the incidence of dengue by 3.38 times greater for experiencing DHF (Sukowinarsih and Cahyati, 2010). The results of research conducted by Nurrochmawati, et al (2017) showed that there was a relationship of the presence of WR with no cover that have the potential to became a place for mosquitoes to breed that was 11.42 times more likely to suffer from HDF. The presence of WR played an important role in the density of the Aedes aegypti mosquito vector, because more and more WR sites would increase the breeding places and would be more densely populated by the Aedes aegypti mosquito (Dash et al, 2012).…”
Section: Multivariate Analysismentioning
confidence: 99%
“…Just as the habit of hanging clothes can increase the number of mosquitoes in the house because mosquitoes prefer to perch on hanging clothes. Based on research conducted by Nurrochmawati (2017) in Nganjuk, it showed that the people who have hanging clothes were more likely to have HDF than subjects who did not have hanging clothes inside their houses.…”
Section: The Effect Of Hanging Clothes On the Incidence Of Hdfmentioning
confidence: 99%
See 3 more Smart Citations